Accumulation of Palmitate in Arabidopsis Mediated by the Acyl-Acyl Carrier Protein Thioesterase FATB1 - Dörmann, Peter (American Society of Plant Physiologists, 2000)
The acyl-acyl carrier protein thioesterase B1 from Arabidopsis (AtFATB1) was previously shown to exhibit in vitro hydrolytic activity for long chain acyl-acyl carrier proteins (P. Dörmann, T.A. Voelker, J.B. Ohlrogge [1995] Arch Biochem Biophys 316: 612–618). In this study, we address the question of which role in fatty acid biosynthesis this enzyme plays within the plant. Over-expression of the AtFATB1 cDNA under a seed-specific promoter resulted in accumulation of high amounts of palmitate (16:0) in seeds. RNA and protein-blot analysis in Arabidopsis and rapeseed (Brassica napus) showed that the endogenous AtFATB1 expression was highest in flowers and lower in leaves. All floral tissues of wild-type plants contained elevated amounts of 16:0, and in the polar lipid fraction of flowers close to 50 mol % of the fatty acids were 16:0. Therefore, flowers contain polar lipids with an unusually high amount of saturated fatty acids as compared to all other plant tissues. Antisense expression of the AtFATB1 cDNA under the cauliflower mosaic virus 35S promoter resulted in a reduction of seed and flower 16:0 content, but no changes in leaf fatty acids. We conclude that the AtFATB1 thioesterase contributes to 16:0 production particularly in flowers, but that additional factors are involved in leaves.